Lanskap Dinamika Skizofrenia: Studi Literatur Terkait Perilaku Pengidap Skizofrenia - Aditya Putra Harwanto; Engki Triwahyudi; Raissa Dwifandra Putri (Flourishing Journal, 2023)
Schizophrenia is a mental disorder involving all psychological aspects that are quite difficult to observe. One of the factors that can cause this disorder is genetic factors. People with schizophrenia have an increased risk of aggressive behavior. Most people with schizophrenia have behavioral disorder impulses in childhood and brain disorders that indicate abnormal neurological development. The purpose of this study is to examine how the landscape dynamics of behavior occur in schizophrenia sufferers with the aim of readers being able to understand symptoms, impacts, patterns of behavior, to intervention steps for people with schizophrenia disorders. Behavior patterns that usually arise in people with schizophrenia are aggressive, impulsive behavior that begins with the appearance of hallucinations and delusions. People with schizophrenia also have apathetic behavior and tend to be anti-social, they prefer to close themselves to their surroundings. Support from family and the surrounding environment is needed by people with schizophrenia. Based on the results of a literature review, it was found that expressive writing therapy also can be used by people with schizophrenia to deal with stress. AbstrakSkizofrenia merupakan suatu gangguan mental yang melibatkan seluruh aspek psikologis yang cukup sulit diamati. Salah satu faktor yang dapat menyebabkan gangguan ini ialah faktor genetik. Orang dengan gangguan skizofrenia memiliki peningkatan risiko untuk berperilaku agresif. Sebagian besar dari orang pengidap skizofrenia memiliki impuls gangguan perilaku pada masa kanak-kanak dan gangguan otak yang menunjukkan perkembangan neurologis abnormal. Adapun tujuan dari penelitian ini ialah mengkaji mengenai bagaimana lanskap dinamika perilaku yang terjadi pada penderita Skizofrenia dengan tujuan pembaca dapat memahami gejala, dampak, pola perilaku, hingga langkah intervensi pada pengidap gangguan skizofrenia. Pola perilaku yang biasa timbul pada pengidap skizofrenia adalah adanya perilaku agresif, impulsif yang diawali dari munculnya halusinasi serta delusi. Pengidap skizofrenia juga memiliki perilaku apatis serta cenderung anti-sosial, mereka lebih suka menutup diri pada lingkungan sekitarnya. Dukungan dari keluarga dan lingkungan sekitar sangat dibutuhkan oleh pengidap skizofrenia. Berdasarkan hasil kajian literatur juga didapatkan bahwa terapi expressive writing dapat digunakan para pengidap skizofrenia dalam mengatasi stres.